The Relationship Between Clinical Supervision Process of Head Nurses and Nursing Outcomes as Perceived by Professional Nurses at Maesod Hospital - Chitnum, Areerut; Daengthern, Laddawan (Journal of The Royal Thai Army Nurses, 2021)
This research is a descriptive research. The purposes of this research were to explore 1) the clinical supervision process of head nurses as perceived by professional nurses at Maesod Hospital, 2) the nursing outcomes as perceived by professional nurses at Maesod Hospital, and 3) the relationship between clinical supervision process of head nurses and nursing outcomes as perceived by professional nurses at Maesod Hospital, The data were analyzed by using frequency, mean, standard deviation, and Spearman Rang Correlation. The results showed that 1) the clinical supervision process of the head nurses as perceived by professional nurses, overall, was at a high level ( = 3.91, S.D = 0.73), 2) the nursing outcomes as perceived by professional nurses, overall, was at a medium level ( = 3.85, S.D = 0.64), 3) the clinical supervision process of the head nurses had a positive relationship at a high level (r = 0.727) with the nursing outcomes as perceived by professional nurses at Maesod Hospital, and it showed a statistical significance at .01